Vinyl-ruthenium entities as markers for intramolecular electron transfer processes - Mücke, Philipp; Linseis, Michael; Zális, Stanislav; Winter, Rainer F. (My University, 2011)
The present account summarizes our work on mononuclear vinyl ruthenium complexes of the type RuCl(CHCHR′)(CO)(PR3)2L, divinyl-bridged diruthenium complexes {RuCl(CO)(PR3)2L}2(μ-CHCH-bridge-CHCH) and on heterobinuclear systems where only one of the two redox-active metal–organic moieties is of the vinyl ruthenium type. The favourable electrochemical properties of the {RuCl(CO)(PR3)2L(CHCH–) tag and the various spectroscopic handles offered by that unit provide detailed insights into the charge and spin delocalization over the {MCl(CO)(PR3)2L} and CHCHR′ constituents in their associated radical cations. They also offer a convenient means for measuring electronic coupling in the mixed-valent radical cations of the homo- and heterodinuclear vinyl-bridged complexes and, under favourable circumstances, on the rate of intramolecular electron transfer between the individual redox sites. Aspects of this work include examples of complexes showing time-dependent valence trapping, complexes aimed at delineating the efficiencies of through-space versus through-bond pathways for electron delocalization, complexes where electrostatic effects on the redox splitting ΔE1/2 dominate over those from the resonance contribution and systems that exhibit extensive charge and spin delocalization between two dislike endgroups despite their intrinsically different redox potentials.
Keywords: Ruthenium; Vinyl complexes; Electrochemistry; Spectroelectrochemistry; Mixed-valent; 540